EMODnet Chemistry Spatial Data Infrastructure for marine observations and related information. (1st December 2018) - Giorgetti, A.; Partescano, E.; Barth, A.; Buga, L.; Gatti, J.; Giorgi, G.; Iona, A.; Lipizer, M.; Holdsworth, N.; Larsen, M.M.; Schaap, D.; Vinci, M.; et al.
Abstract: Scientific research as well as management of the marine environment, and sustainable blue growth are based on the availability of quality-assured observations, reliable data and solid scientific-based information. These represent three consecutive steps of Data-Information-Knowledge-Wisdom paradigm on the pyramid of wisdom, providing different layers of information. EMODnet (European Marine Observation and Data network) is one of the key infrastructures engaged in collecting, facilitating access and promoting use and re-use of marine observation and data products for both scientific research and marine environmental management. Its Spatial Data Infrastructure (SDI) represents a powerful mechanism to support the implementation of the Marine Strategy Framework Directive Article 19.3 in accordance with the INSPIRE Directive standards and implementing rules. Standardized, harmonized and validated chemical data collections are made available for water quality evaluation at a regional scale, establishing interoperability between the data sets from the many different providers (more than 60 in EMODnet Chemistry). Concentration maps of nutrients, chlorophyll-a and dissolved oxygen are computed on a standard grid, providing information at a regular time interval, per season and over several vertical layers, including the deepest one. Dedicated Open Geospatial Consortium standard services for browsing, viewing and downloading chemistry observation data and data products for the European waters have been developed, and are actively maintained and monitored. These results can provide knowledge layers and can also answer the needs of the directive on Maritime Spatial Planning (EU, 2014), which requires the integration of multidisciplinary data and information on the state of the marine environment with maritime and human activities. Highlights: Results achieved by the EMODnet Chemistry and the viewing services developed to download and share them. Observations and information are discussed, in relation to MSFD, INSPIRE Directive standards and Maritime Spatial Planning. Data availability is an important component of the MSP process for environmental management of protected areas. In the framework of EMODnet Chemistry, 160 maps were realized, covering 11 parameters, 4 seasons and aggregated for 30 depth.